Total ergonomics approach to analyze work system and propose improvements for increasing worker productivity - Suparti, Erni; Wahyudi, Adhie Tri; Fitrianingsih, Ana (OPSI, 2023)
UD. TGM is one of SMEs located in Blora, Central of Java. They can produce 60 – 150 pallets of paving block per hour. Based on observations and measurements, the noise level around production machines is above 90 dB and the temperature around UD. TGM reaches 34°C. Those conditions do not match with the regulatory standards by Ministry of Health of Republic Indonesia. In addition, based on NBM questionnaire, there were 10 complaints of very sick, 7 complaints of pain, and 7 complaints of moderate pain. The worker's cardiovascular load was 36.4% (or needed improvement). Based on the REBA assessment informed that a corrective action needs to be taken immediately. This study aims to analyze the work system totally and provide improvement recommendations. We proposed recommendations by total ergonomics approach collaborated with fishbone diagrams, tree diagrams, and PDPC diagrams. The recommendations were UD. TGM need to create a supervisory team, create work instructions, design additional of transportation tools like a hand stacker, replace dirt floors with paving, enlarge air ventilation holes and add roof height. Then, the evaluation of the recommendations by Catia software, the REBA score was reduced from level 3 to level 1 (or low risk).